RELATIONSHIP BETWEEN PERSONAL INFORMATION SERVICES AND SELF-EFFIICACT STUDENTS OF SMP NEGERI 22 JAMBI - Walindarahma, Sri Annisa Walindarahma (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2023)
Self-efficacy is the belief in an individual's ability to succeed in carrying out a particular task and this ability influences the belief in trying and maintaining it. Where self-efficacy can be influenced by personal information services including personal goals, achieving developmental tasks, socializing with the environment and adapting to the environment. The purpose of this study was to find out how the relationship between personal information services and the self-efficacy of SMP Negeri 22 Jambi City students. This research is a quantitative study using a correlation approach with Pearson product moment correlation analysis. The population in this study were students of class VII SMP Negeri 22 Jambi City. The sampling used random sampling technique with a total of 52 students. The data collection tool in this study was a questionnaire which had 22 items on personal information service variables and 20 items for self-efficacy. The data analysis techniques used were the normality test, linearity test and correlation analysis test. The results showed that there was a relationship between personal information services and the self-efficacy of students at SMP Negeri 22 Jambi City with the result that the percentage of personal information services was 83% and the results of the analysis of the percentage of self- efficacy was 74.2%. And the results of the correlation analysis show that there is a significant relationship between the personal information service variable and student self-efficacy with a value of 0.443 which is in a moderate correlation or adequate relationship.